2020
DOI: 10.1038/s41374-020-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

Early pathogenesis of cystic fibrosis gallbladder disease in a porcine model

Abstract: Hepatobiliary disease causes significant morbidity in people with cystic fibrosis (CF), yet this problem remains understudied. We previously found that newborn CF pigs have microgallbladders with significant luminal obstruction in the absence of infection and consistent inflammation. In this study, we sought to better understand the early pathogenesis of CF pig gallbladder disease. We hypothesized that loss of CFTR would impair gallbladder epithelium anion/liquid secretion and increase mucin production. CFTR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 81 publications
4
13
0
Order By: Relevance
“…Our studies also found that CF intrahepatic biliary organoids had defective fluid secretion. This is consistent with our studies in the CF pig gallbladder (Zarei et al, 2020). The exact function of biliary fluid secretion, specifically pertaining to CFTR, is still not clear, but likely contributes to decreased bile flow in CF pigs (Uc et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our studies also found that CF intrahepatic biliary organoids had defective fluid secretion. This is consistent with our studies in the CF pig gallbladder (Zarei et al, 2020). The exact function of biliary fluid secretion, specifically pertaining to CFTR, is still not clear, but likely contributes to decreased bile flow in CF pigs (Uc et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Organoids were kept in suspension at 4ºC while they were permeabilized in 0.3% Triton for 1 h and blocked in Superblock (Thermo Fisher) with 4% normal goat serum for 48 h. Organoids were then incubated with primary antibodies overnight: mouse anti‐CFTR (clone 769) (1:100 dilution, University of North Carolina—Chapel Hill and the Cystic Fibrosis Foundation Therapeutics) and rabbit anti‐Na + /K + ‐ATPase (clone EP1845Y) (1:100 dilution, Abcam). The anti‐CFTR antibody was validated based on cellular localization, absent signal in CFTR‐deficient tissue, and previous studies (Zarei et al, 2020). The anti‐Na + /K + ‐ATPase was validated based on cellular localization and previous studies (Nieto‐Torres et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations